The Correlation of Diabetes Mellitus and Urinary Retention From Intravesical OnabotulinumtoxinA Injection for Overactive Bladder. Issue 5 (21st May 2023) - Takashima, Yoko; Handler, Stephanie; Laus, Katharina; Eckhardt, Sarah; Whitaker, Taylor; Tenggardjaja, Christopher; Yazdany, Tajnoos
Abstract : Importance and Objectives: The objective was to determine whether patients with diabetes mellitus (DM) treated with intravesical onabotulinumtoxinA (BoNT) injection for overactive bladder (OAB) had increased urinary retention requiring clean intermittent catheterization (CIC), as well as the impact of disease duration and severity. We hypothesize that patients with DM will have higher rates of retention after BoNT injection. Study Design: We performed a retrospective cohort analysis of women in the Kaiser Permanente Southern California Health System who underwent BoNT injection for OAB, excluding women with a history of urinary retention or neurogenic bladder. Results: We identified 565 patients, 410 in the control group and 155 in the DM group. No significant difference was found in the rate of CIC (9% in the control group versus 5.8% in the DM group, P = 0.2), voiding dysfunction, and peak postprocedure postvoid residual volume (PVR). Patients with diabetes had a significantly increased rate of postprocedure urinary tract infection (UTI; 27.6% versus 38.1%, P = 0.02). Urinary tract infection was significantly associated with urinary retention (adjusted odds ratio [OR], 2.26; 95% confidence interval [CI], 1.02–4.99; P = 0.045) and peak PVR ≥200 mL (adjusted OR, 2.42; 95% CI, 1.15–5.06; P = 0.019). Diabetic disease duration and severity were not a predictor of urinary retention, elevated PVR, or voiding dysfunction; however, the presence of ≥1 disease-related complication was a predictor of UTI (adjusted OR, 2.81; 95% CI, 1.34–5.91; P = 0.006). Conclusions: Diabetic patients had a similar rate of urinary retention requiring CIC after BoNT injection for OAB compared with nondiabetic patients. Diabetic patients had an increased risk of UTI based on disease severity.